Development of the Integrity Zone of the Ministry of Religious Affairs Office of Magetan Regency: A Process, Challenges, and Strategies Towards a Corruption-Free Area - Indah Kurniawati (AMUYA: JOURNAL OF MANAGEMENT, 2025)
This policy paper describes that implementation of Bureaucratic Reform (RB) in several Work Units is often still administrative in nature due to a limited understanding of the substance of the area of change. This condition causes a discrepancy between internal assessments and the reality of public services, so that the objective of establishing an Integrity Zone (ZI) towards a Corruption-Free Zone (WBK) has not been fully achieved. To understand these dynamics, a qualitative method was used with Strengths, Weaknesses, Opportunities, and Threats (SWOT) analysis. The results of the analysis show that the main strengths lie in the formation of the ZI Work Team in the Work Unit, the existence of an internal control mechanism by the Internal Assessment Team (TPI) of the Ministry of Religious Affairs, and the existence of rewards for successfully achieving the WBK predicate. However, weaknesses emerged in the form of low understanding among the State Civil Apparatus (ASN) of the substance of the 6 areas of change and their indicators, and the Evaluation Worksheet (LKE) was only filled out administratively. In terms of opportunities, there are national regulations and policies related to RB and ZI, opportunities to learn from other agencies that have successfully achieved WBK, and developments in information technology that support data openness and public service innovation. Meanwhile, threats come from external oversight by the media or Non-Governmental Organization (NGO), as well as competition in achieving WBK with other work units. In conclusion, the implementation of ZI development at the Magetan District Ministry of Religious Affairs Office has so far been stuck in an administrative approach.